An application of Tawhidic paradigm in macro-planning of the 1 Malaysia policy - Sarif, Suhaimi Mhd; Ismail, Yusof (2011)
It is a great challenge for the Muslims in particular to relate the inherent universality of Tawhid to the multi-racial, multi-religion context. This paper aims to relate proposed components of a Tawhidic paradigm to hypothetical, and yet feasible macro management of the 1-Malaysia policy. It defines the paradigm and explains its key components. Next, it explains the concept of “1 Malaysia: People First and Performance Now” (PFPN) policy. After that, the paper explains how to apply the paradigm to the Malaysian government policy. In integrating the spirit of Tawhid into a government policy, such as 1 Malaysia, the policy implementers who themselves may not necessarily belong to the same faith will still be able to achieve the overall intent of the government, while respecting the respective faiths of citizens.